Partycypacja społeczna na tle zasady zrównoważonego rozwoju - Dziuba, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The problems of sustainable development take on meaning in proportion to growth of the meaning of these problems, which result from disrespect of principle of sustainable development. The matters of drawing out of resources, irrational using of them, inappropriate management of wasters, the unbalanced consumption are clearly perceptible through these problems, which appear as result from applying the simply and short-term logic of profit. In last years however, especially after financial crisis from 2008 it is quite clear, that the logic of free market is not appropriate to manage of supplies and to create stable and sustainable economic growth. In order to solve these problems and create the terms of sustainable development, it is necessary to create the mechanisms of social participation. The social commitment, which is evidence of responsibility and using a social potential can be tool to direct of social-economic development to more reasonable and sustainable tendency.
Keywords: partycypacja społeczna; zrównoważony rozwój; wolny rynek